INTEGRATING SERVICE VALUE CHAIN GOVERNANCE ON SMALL SUNFLOWER PROCESSING INDUSTRIES IN DODOMA, TANZANIA - Sama, Hamisi; Mashenene, Andrew J. (Applied Studies in Agribusiness and Commerce, 2025)
Small-scale sunflower oil processors dominate Tanzania’s sunflower value chain but face persistent performance challenges. This study examines how service value chain governance – defined by factors such as transaction complexity, service characteristics, technological capabilities, market transparency, market structure, and institutional frameworks – influences the capabilities and performance of small sunflower processing industries in Dodoma. Drawing on global value chain and transaction cost economics theories, we hypothesize that high transaction complexity and service intangibility negatively impact processors’ technological and human resource capabilities, while robust technological capacity and market transparency improve logistics and marketing performance. A cross-sectional survey of 275 sunflower oil processors in Dodoma was conducted, and six multiple regression models were used to test each specific hypothesis. Results show that all six governance factors significantly affect the processors’ operational capabilities in the expected directions. High transaction complexity and service heterogeneity are associated with lower technological competency and workforce efficiency, whereas greater technological capability and market transparency yield improved logistical coordination and market access. Fragmented market structures (many small suppliers) correlate with weaker financial performance, and a strong institutional framework is linked to better regulatory compliance. These findings highlight critical governance-related barriers and enablers for small agro-processors. We discuss practical and managerial implications for improving value chain integration – including investing in technology, training, and policy support – and outline theoretical contributions.